Radiation exposure and fluoroscopy time in mechanical thrombectomy of anterior circulation ischemic stroke depending on the interventionalist’s experience: a retrospective single center experience - Weyland, Charlotte S.; Hemmerich, Felix; Möhlenbruch, Markus Alfred; Bendszus, Martin; Pfaff, Johannes (European radiology, 2020)
To quantify the influence of interventionalist’s experience on procedure time, radiation exposure, and fluoroscopy time during mechanical thrombectomy (MT) in the anterior circulation.